Professional Commitment: Transformational Leadership, Perceived Organizational Support, and Achievement Motivation as the Mediator - Dian Wulandari; Pipit Noviani; S. Hardhienata; Sri Setyaningsih (STAI Hubbulwathan Duri, 2023)
The main objective of this study is to formulate practical ways in increasing professional commitment based on studies on the influence of transformational leadership, Perceived Organizational Support (POS), and achievement motivation as mediators, toward professional commitment. This research was conducted at an Elementary Public School in Klari District, Karawang Regency, using quantitative methods with a path analysis approach. The population in this study was all 278 PNS Elementary Public School Teachers in Klari, and the study sample was 165 people obtained by simple random sampling. The results of the survey at the significance level of 5% showed that: (1) transformational leadership has a direct positive effect on professional commitment (βy1= 0.190), (2) POS has a direct positive effect on professional commitment (βy2 = 0.251), (3) achievement motivation has a direct positive effect on professional commitment βy3= 0.094, (4) transformational leadership had a positive effect on achievement motivation (βy31 = 0.208), (5) POS had a direct positive effect on achievement motivation (βy32 = 0.276), (6) Achievement motivation effectively mediated the transformational leadership and POS on professional commitment. Based on the analysis, it can be recommended that the order of indicators that need to be improved immediately are: working conditions, supervisor support, and organizational rewards (from POS); Individualized consideration (from Transformational Leadership); responsibility and superior drive (from achievement motivation).